Genome-Wide Evidence for Complex Hybridization and Demographic History in a Group of Cycas From China - Tao, Yueqi; Chen, Bin; Kang, Ming; Liu, Yongbo; Wang, Jing (Frontiers in Genetics, 2021)
Cycads represent one of the most ancestral living seed plants as well as one of the most threatened plant groups in the world. South China is a major center and potential origin of Cycas, the most rapidly diversified lineage of cycads. However, genomic-wide diversity of Cycas remains poorly understood due to the challenge of generating genomic markers associated with their inherent large genomes. Here, we perform a comprehensive conservation genomic study based on restriction-site associated DNA sequencing (RADseq) data in six representative species of Cycas in South China. Consistently low genetic diversity and strong genetic differentiation were detected across species. Both phylogenetic inference and genetic structure analysis via several methods revealed generally congruent independent groups among the six Cycas species. The analysis with Admixture showed low mixing of genetic composition among species, while individuals of C. dolichophylla exhibited substantial genetic admixture with C. bifida, C. changjianensis, and C. balansae. Furthermore, the results from Treemix, f4-statistic, and ABBA-BABA test were generally consistent and revealed the complex patterns of interspecific gene flow. Relatively strong signals of hybridization were detected between C. dolichophylla and C. szechuanensis, and the ancestor of C. taiwaniana and C. changjiangensis. Distinct patterns of demographic history were inferred for these species by Stairway Plot, and our results suggested that both climate fluctuation and frequent geological activities during the late Pleistocene exerted deep impacts on the population dynamics of these species in South China. Finally, we explore the practical implications of our findings for the development of conservation strategies in Cycas. The present study demonstrates the efficiency of RADseq for conservation genomic studies on nonmodel species with large and complex genomes. Given the great significance of cycads as a radical transition in the evolution of plant biodiversity, our study provides important insights into the mechanisms of diversification in such recently radiated living fossil taxa.